Cover Feature: Towards operando IR‐ and UV‐vis‐Spectro‐Electrochemistry: A Comprehensive Matrix Factorisation Study on Sensitive and Transient Molybdenum and Tungsten Mono‐Dithiolene Complexes (Chemistry ‐ Methods 1/2021). Issue 1 (23rd December 2020) - Elvers, Benedict J.; Sawall, Mathias; Oberem, Elisabeth; Heckenberger, Kilian; Ludwig, Ralf; Neymeyr, Klaus; Schulzke, Carola; Krewald, Vera; Fischer, Christian
Abstract : The Cover Feature shows that the spectroelectrochemical methods simultaneously record spectral and electrochemical data that often contain more chemical information than can be conveniently analysed. In this work, we present a method for the extraction of individual chemical signatures from single‐run spectroelectrochemical measurements. In combination with computational chemistry, this new approach will likely be helpful to better understand the electrochemistry of a wide range of molecular complexes. The cover was designed by J. J. Wending. More information can be found in the Full Paper by Benedict J. Elvers et al .